2013
DOI: 10.1002/elsc.201200189
|View full text |Cite
|
Sign up to set email alerts
|

β‐poly(l‐malic acid) production by fed‐batch culture of Aureobasidium pullulans ipe‐1 with mixed sugars

Abstract: Research Article β-poly(L-malic acid) production by fed-batch culture of Aureobasidium pullulans ipe-1 with mixed sugars β-poly(l-malic acid) (PMLA) is a biopolyester, which has attracted growing attention due to its potential applications in medicine and other industries. In this study, the biosynthetic pathway of PMLA and the fermentation strategies with mixed sugars were both investigated to enhance PMLA production by Aureobasidium pullulans ipe-1. Metabolic intermediates and inhibitors were used to study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…To measure the amount of total malic acid (including PMLA and free malic acid), 1 mL of supernatant was incubated with 1 mL of 2 mol L −1 H 2 SO 4 for 12 h at 90°C. After neutralization of the solution, L‐malic acid concentration was measured by a HPLC apparatus (Shimadzu LC20AT) as described in Cao et al , except for equipping with an Aminex HP‐X87H lon Exclusion column and H 2 SO 4 as moving phase. The process was performed at a temperature of 40°C, a flow rate of 0.6 mL min −1 , an absorbance wavelength of 210 nm and with 5 mmol L −1 H 2 SO 4 as moving phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the amount of total malic acid (including PMLA and free malic acid), 1 mL of supernatant was incubated with 1 mL of 2 mol L −1 H 2 SO 4 for 12 h at 90°C. After neutralization of the solution, L‐malic acid concentration was measured by a HPLC apparatus (Shimadzu LC20AT) as described in Cao et al , except for equipping with an Aminex HP‐X87H lon Exclusion column and H 2 SO 4 as moving phase. The process was performed at a temperature of 40°C, a flow rate of 0.6 mL min −1 , an absorbance wavelength of 210 nm and with 5 mmol L −1 H 2 SO 4 as moving phase.…”
Section: Methodsmentioning
confidence: 99%
“…The culture broth (8 mL) was centrifuged at 10 000 × g for 8 min and the resulting supernatants was used for the measurement of PMLA and glucose. For the measurement of biomass content, the cells were washed three times with 8 mL of distilled water, then dried to constant weight at 90 ∘ C. To measure the amount of total malic acid (including PMLA and free malic acid), 1 mL of supernatant was incubated with 1 mL of 2 mol L −1 H 2 SO 4 for 12 h at 90 ∘ C. After neutralization of the solution, L-malic acid concentration was measured by a HPLC apparatus (Shimadzu LC20AT) as described in Cao et al, 10…”
Section: Analytic Methodsmentioning
confidence: 99%
“…Moreover, the researcher speculated that the metabolic pathway of PMLA may vary in different strains. The research found that PMLA production is considerably associated with the glyoxylate pathway in Physarum polycephalum with the addition of intermediates and inhibitors (Lee et al 1999 ) , and it can also be catalyzed by nonbiotin-dependent carboxylation, which is related to the rTCA pathway in A. pullulan (Cao et al 2014). Due to the varied biosynthesis pathways for PMLA production, it is challenging to construct the genetically engineered strains.…”
Section: Introductionmentioning
confidence: 99%
“…PMLA has outstanding features as biocompatibility, biodegradability, water solubility, absorbability, nonimmunogenicity and easy chemical modification [1]. Therefore, PMLA and its derivatives may have great potential for applications in the drug delivery field and the production of advanced biomaterials [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…To meet the increasing demand for PMLA, it has become necessary to improve the efficiency of PMLA production. Numerous approaches have been developed to improve PMLA production, including screening for high-yield mutant strains, investigating improvements to fermentation modes and strategies, optimisation of carbon sources, adding exogenous substances and control of agitation speed [3,7,8]. In our study, we have focussed on developing methods to weaken the resistance of cells to the movement of substances into/out of them and to enhance PMLA production.…”
Section: Introductionmentioning
confidence: 99%